Institutional and capacity challenges in agricultural policy process: The case of Democratic Republic of Congo - Ragasa, Catherine; Babu, Suresh Chandra; Ulimwengu, John M. (International Food Policy Research Institute, 2011)
This paper is an exploratory study that looks at early stages of the decentralization and other reforms in the policymaking and planning processes in the Democratic Republic of Congo (DRC). The paper develops a conceptual framework and adopts an innovative mapping tool to identify capacity and incentive challenges impeding the effective design and implementation of policy processes. Findings suggest that the decentralized platform, through the Agriculture and Rural Management Councils, has shown some improvement in civil society participation in local-level and national-level policy and planning processes; however, these councils are being threatened by sustainability of funds and lack of demonstrated benefits and impact of participation. The weak institutions for managing, coordinating, overseeing, and monitoring seriously hinder the attainment of an evidence-based and inclusive policy process. Findings also suggest an alarmingly inadequate and aging staff in key public-sector organizations both at the national and local levels, which warrants an urgent and speedy design and implementation of the civil service and human resource reform process to accelerate recovery and development in the economy. This paper concludes with specific suggestions and considerations for priority actions to address the institutional challenges in the reform process and strategic training investments. Finally, we identify key areas for future research.